(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Paratrochosina amica is an Allocosinae wolf spider species that inhabits grasslands and gardens in Uruguay and southern South America, where it has a wide distribution. In this study, we extended the representation of genetic data from previous studies by including specimens that cover most of the distribution range. Conversely to what has been reported for other species of the subfamily, P. amica shows similar body sizes in both sexes and males are the mobile sex that initiates courtship. As we are trying to understand the factors shaping sexual behaviour and size dimorphism in Allocosinae, studies in P. amica are crucial. We analysed the phylogenetic relationships and genetic diversity in this species. The analysis corroborated the monophyly of Allocosinae and P. amica, which is also located in the same phylogenetic position as reported in previous studies. The haplotype network suggests high connectivity between individuals from the studied localities. Finally, the GMYC analysis showed that the individuals belong to the same evolutionary lineage.